The effects of emotional intelligence towards work commitment among employees at KSL Resort & Hotel, Johor Bahru / Siti Aishah Buniran - Buniran, Siti Aishah (2014)
Emotional intelligence now regarded as one of the importance concepts that could lead to organizational success. The words organization success itself shows that emotional intelligence could bring positive impact toward organization in many possible ways. For example according to Dulewicz Victor in his journal “Leadership At The Top: The Need For Emotional Intelligence In Organizations, he explains about the importance of emotional intelligence for effective leadership especially toward top management. Emotional intelligence also has the potential to affect employee job performance subsequently on organizational success. However the amount of emotional intelligence that could lead to organizational success will be varied depends on different demographics factors. (Rahim et all, 2010). In order to studies about the relationship between emotional intelligence and job performance, research has been conducted at KSL RESORT & HOTEL which located in the heart of Johor Bahru. KSL RESORT & HOTEL main business is to provide accommodation to tourist who came to Johor Bahru. Thus, to deal and fulfill the needs of customers and guest from different parts of the country and placed definitely required emotional intelligence in oneself. Therefore, the data and information will be collected from this company and being sample to study the relationship between emotional intelligence and job performance.